Reconstruction of the Functional Relationship Between Criminal Procedure Law and Material Criminal Law from the Perspective of the National Criminal Code and the Latest Criminal Procedure Code - Eva Berta Pattinasarany; Binsar Jon Vic S (International Journal of Social Service and Research, 2026)
The reform of Indonesia’s criminal law system through the enactment of Law Number 1 of 2023 concerning the Criminal Code and Law Number 20 of 2025 concerning the Criminal Procedure Code represents a significant transformation in the development of the national criminal justice system. However, changes to substantive criminal law have not been fully synchronized with procedural mechanisms, creating potential challenges in determining criminal liability, administering evidence, and applying restorative justice principles. This research aimed to analyze the functional relationship between substantive criminal law and criminal procedure law and to formulate a reconstruction framework that supports an integrated criminal justice system. This study employed a normative legal research method using statutory, conceptual, and legal-system approaches. The legal sources consisted of primary legal materials, including relevant legislation, and secondary legal materials derived from scholarly publications, legal literature, and expert opinions. The legal materials were analyzed qualitatively using grammatical, systematic, and teleological methods of interpretation. The results indicate that, although the new Criminal Code introduces progressive concepts, such as expanded corporate criminal liability, recognition of living law, and restorative justice-oriented sentencing objectives, the Criminal Procedure Code does not yet provide adequate procedural mechanisms to fully support these developments. The findings emphasize the need for harmonization through the adoption of implementing regulations, the strengthening of evidentiary procedures, the enhancement of judicial oversight, and the integration of restorative justice mechanisms. This research concludes that reconstructing the functional relationship between substantive criminal law and criminal procedure law is essential to establishing a consistent, proportionate, and human rights-based criminal justice system in Indonesia